2018
DOI: 10.1016/j.juro.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Dysfunction and Associated Pons Volume in Patients with Wolfram Syndrome

Abstract: A significant number of children, adolescents and young adults with Wolfram syndrome have objective evidence of lower urinary tract dysfunction. Decreased pons volume is associated with more abnormal urinary function and lower quality of life in patients with Wolfram syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
(43 reference statements)
0
14
0
2
Order By: Relevance
“…respiration, urination) known to be affected in Wolfram syndrome. In fact, in a cross-sectional, correlational analysis, we found that ventral pons volume correlated with the degree of urinary dysfunction 30 . In addition, gait and balance, which are associated with the cerebellum, are known to be abnormal in Wolfram syndrome, even at the early stages of the disease process 7,8 .…”
Section: Discussionmentioning
confidence: 75%
“…respiration, urination) known to be affected in Wolfram syndrome. In fact, in a cross-sectional, correlational analysis, we found that ventral pons volume correlated with the degree of urinary dysfunction 30 . In addition, gait and balance, which are associated with the cerebellum, are known to be abnormal in Wolfram syndrome, even at the early stages of the disease process 7,8 .…”
Section: Discussionmentioning
confidence: 75%
“…La progresión normal como lo revela el estudio de este paciente indica que la mayoría desarrollará casi todas las complicaciones de la enfermedad (15), conviene mencionar además que las complicaciones neurológicas suelen aparecer alrededor de la cuarta década de la vida y son las que confieren mal pronóstico porque acortan la esperanza de vida (16); por tanto el tratamiento se basa en tratar las afecciones, pues no existen medidas curativas (5). La principal limitación del establecimiento del diagnóstico es la falta de análisis genético, que no se realiza en Ecuador.…”
Section: Discussionunclassified
“…6,8,23 Urinary tract problems, including dilation of the urinary tracts, neurogenic bladder, and urinary incontinence, have been reported in 19% of patients with WS, but this figure is likely to represent an underestimate. 23,25 There is evidence that lower pontine volume on magnetic resonance imaging (MRI) is associated with more severe urinary tract dysfunction and lower quality of life in WS. 25 With greater access to genetic testing and the application of next-generation sequencing in clinical practice, there is increasing recognition of a subgroup of patients who harbor heterozygous dominant pathogenic variants in the WFS1 gene.…”
Section: Molecular Genetics and Clinical Features Of Wolfram Syndromementioning
confidence: 99%
“…23,25 There is evidence that lower pontine volume on magnetic resonance imaging (MRI) is associated with more severe urinary tract dysfunction and lower quality of life in WS. 25 With greater access to genetic testing and the application of next-generation sequencing in clinical practice, there is increasing recognition of a subgroup of patients who harbor heterozygous dominant pathogenic variants in the WFS1 gene. [17][18][19] These are more often missense pathogenic variants, compared to the loss-of-function variants and deletions identified in patients with recessive WFS1 mutations.…”
Section: Molecular Genetics and Clinical Features Of Wolfram Syndromementioning
confidence: 99%